ปัญหาการดำเนินนโยบายด้านเบี้ยยังชีพตามโครงการสร้างหลักประกันรายได้ของผู้สูงอายุ ในเขตตำบลหนองไผ่ อำเภอชุมแพ จังหวัดขอนแก่น - หัสจันทอง, วีระยา (วารสารศรีล้านช้างปริทรรศน์, 2017)
บทความนี้มีวัตถุประสงค์ ดังนี้ 1) เพื่อศึกษาปัญหาการดำเนินนโยบายด้านเบี้ยยังชีพ      ตามโครงการสร้างหลักประกันรายได้ของผู้สูงอายุในเขตตำบลหนองไผ่ อำเภอชุมแพ จังหวัดขอนแก่น2) เพื่อเปรียบเทียบปัญหาการดำเนินนโยบายด้านเบี้ยยังชีพในเขตตำบลหนองไผ่ อำเภอชุมแพ จังหวัดขอนแก่น ตามโครงการสร้างหลักประกันรายได้ของผู้สูงอายุ และ 3) เพื่อศึกษาข้อเสนอแนะการดำเนินนโยบายด้านเบี้ยยังชีพตามโครงการสร้างหลักประกันรายได้ของผู้สูงอายุในเขตตำบล  หนองไผ่ อำเภอชุมแพ จังหวัดขอนแก่น กลุ่มตัวอย่างที่ใช้ในการศึกษา คือ ผู้สูงอายุที่ได้รับเบี้ยยังชีพตามโครงการสร้างหลักประกันรายได้ของผู้สูงอายุในเขตตำบลหนองไผ่ อำเภอชุมแพ จังหวัดขอนแก่น จำนวน 308 คน โดยใช้สูตรของทาโร่ ยามาเน่ (Taro Yamane) เครื่องมือที่ใช้ในการเก็บรวบรวมข้อมูลครั้งนี้ คือ แบบสอบถาม (Questionnaire) มีลักษณะเป็นแบบตรวจเช็ครายการ (Check List) การวิเคราะห์ข้อมูล โดยใช้ค่าความถี่ (Frequency) ค่าร้อยละ (Percentage) ค่าเฉลี่ย (Mean)      ค่าส่วนเบี่ยงเบนมาตรฐาน (Standard Deviation) สถิติที่ใช้ในการวิเคราะห์ความแตกต่างของค่าเฉลี่ยประชากร (Independent t-test) และ F-test หรือ (One-way ANOVA)           ผลการวิจัยพบว่า 1) ปัญหาการดำเนินนโยบายด้านเบี้ยยังชีพตามโครงการสร้างหลักประกันรายได้ของผู้สูงอายุตำบลหนองไผ่ อำเภอชุมแพ จังหวัดขอนแก่น โดยรวมทั้ง 3 ด้านอยู่ในระดับมาก เมื่อพิจารณารายด้าน โดยเรียงตามค่าเฉลี่ยจากมากไปน้อย ด้านที่มีค่าเฉลี่ยมากที่สุด คือ ด้านวิธีการจ่ายเงินและการสิ้นสุดการได้รับเงินเบี้ยยังชีพผู้สูงอายุ รองลงมาได้แก่ ด้านขั้นตอนการยื่นคำขอและการตรวจสอบผู้มีสิทธิ์รับเงินเบี้ยยังชีพผู้สูงอายุ ส่วนด้านที่มีค่าเฉลี่ยน้อยที่สุด คือ ด้านคุณสมบัติของผู้มีสิทธิได้รับเงินเบี้ยยังชีพผู้สูงอายุ 2) ผลการเปรียบเทียบปัญหาการดำเนินนโยบายด้านเบี้ยยังชีพตามโครงการสร้างหลักประกันรายได้ของผู้สูงอายุตำบลหนองไผ่ อำเภอชุมแพ จังหวัดขอนแก่น พบว่า ผู้สูงอายุที่ได้รับเบี้ยยังชีพ ที่มีเพศและระดับการศึกษาต่างกัน มีความคิดเห็นต่อการดำเนินนโยบายด้านเบี้ยยังชีพตามโครงการสร้างหลักประกันรายได้ของผู้สูงอายุตำบลหนองไผ่อำเภอชุมแพ จังหวัดขอนแก่น ไม่แตกต่างกัน ส่วนผู้สูงอายุที่ได้รับเบี้ยยังชีพที่มีอายุต่างกัน มีความคิดเห็นต่อการดำเนินนโยบายด้านเบี้ยยังชีพตามโครงการสร้างหลักประกันรายได้ของผู้สูงอายุตำบลหนองไผ่ อำเภอชุมแพ จังหวัดขอนแก่น แตกต่างกันอย่างมีนัยสำคัญทางสถิติที่ระดับ 0.05 3) ข้อเสนอแนะเกี่ยวกับการดำเนินนโยบายด้านเบี้ยยังชีพตามโครงการสร้างหลักประกันรายได้ของผู้สูงอายุตำบลหนองไผ่ อำเภอชุมแพ จังหวัดขอนแก่น มีรายละเอียดดังนี้ (1) ด้านคุณสมบัติของผู้มีสิทธิ์ได้รับเงินเบี้ยยังชีพผู้สูงอายุ พบว่า ปัญหาที่พบมาก คือ ขาดการประชาสัมพันธ์ให้เข้าใจเกี่ยวกับคุณสมบัติของผู้ที่จะได้รับเบี้ยยังชีพผู้สูงอายุ รองลงมาคือผู้นำชุมชน ขาดการประสานงานเกี่ยวกับการจัดการที่ผู้สูงอายุจะได้รับเบี้ยยังชีพ และไม่มีเอกสาร แผ่นพับ ใบปลิว แจกให้ผู้สูงอายุ ส่วนด้านแนวทางแก้ไข พบว่ามากที่สุดคือ ให้องค์กรปกครองส่วนท้องถิ่น ประชาสัมพันธ์ให้ประชาชนทราบให้เข้าใจถึงคุณสมบัติ และเอกสารที่ต้องใช้ในการรับเบี้ยยังชีพผู้สูงอายุ รองลงมาคือ ผู้นำชุมชน ต้องมีการประชาสัมพันธ์ผ่านลำโพงประชาสัมพันธ์ของหมู่บ้าน     และควรมีเอกสาร หรือข้อมูลอื่น ๆ ที่เกี่ยวข้องแจกไว้ให้ผู้สูงอายุ หรือลูกหลานได้รับทราบ (2)  ด้านขั้นตอนการยื่นคำขอและการตรวจสอบสิทธิ์รับเงินเบี้ยยังชีพผู้สูงอายุ ปัญหาที่พบมากที่สุดคือขาดการประชาสัมพันธ์ถึงขั้นตอนในการยื่นคำขอ เอกสาร และขั้นตอนการตรวจสอบสิทธิ์ และขาดการเผยแพร่ข้อมูลข่าวสาร หรือขั้นตอนการรับเบี้ยยังชีพให้กับผู้สูงอายุรับรู้  ส่วนด้านแนวทางแก้ไข พบว่ามากที่สุดคือ ประชาสัมพันธ์และซักซ้อมความเข้าใจถึงขั้นตอนต่าง ๆ ในการรับเบี้ยยังชีพ   ให้กับผู้นำชุมชน แล้วให้ผู้นำชุมชนไปประชาสัมพันธ์แก่ผู้สูงอายุ รองลงมาคือควรมีข้อมูลให้ลูกหลานได้รับรู้ด้วย และประกาศหรือประชาสัมพันธ์ให้ประชาชนได้ทราบบ่อย ๆ และ (3) ด้านวิธีการจ่ายเงินและการสิ้นสุดการได้รับเงินเบี้ยยังชีพผู้สูงอายุ ปัญหาที่พบมากที่สุดคือความล่าช้าในการจ่ายเบี้ยยังชีพ รองลงมาคือขาดการประชาสัมพันธ์ให้ทายาทผู้เสียชีวิตทราบ และถ้าผู้สูงอายุเสียชีวิตในกลางเดือนให้ได้รับเบี้ยยังชีพ ส่วนด้านแนวทางแก้ไข พบว่ามากที่สุดคือบอกขั้นตอน หรือระเบียบวิธีการให้ประชาชนทราบ รองลงมาคือกำหนดวันที่แน่นอนในการจ่ายเบี้ยยังชีพในแต่ละเดือน และให้สิทธิ์ผู้เสียชีวิตได้รับเบี้ยยังชีพครั้งสุดท้าย The objectives of the research were (1) to study problems of policy implementation on cash allowance provision under the elderly income guarantee project in Nong Phai sub-district, Chum Phae district, Khon Kaen province, (2) to compare some problems of policy implementation on cash allowance provision under the elderly income guarantee project in Nong Phai sub-district, Chum Phae district, Khon Kaen province, and (3) to study recommendations on problems of policy implementation on cash allowance provision under the elderly income guarantee project in Nong Phai sub-district, Chum Phae district, Khon Kaen province. The research population was a total of the elderly receiving cash allowance under the state-run elderly income guarantee project in Nong Phai sub-district, Chum Phae district, Khon Kaen province, and the sampling size of 308 samples were selected and determined by Taro Yamane’s calculation formula. The research instruments used for data collection were the checklist questionnaire. The data were analyzed by the statistics comprised of frequency distribution, percentage, arithmetic mean, and standard deviation. The mean differences of the population were analyzed by the independent T-test method.             The research of research were found as follws:           1) Problems of policy implementation on cash allowance provision under the elderly income guarantee project in Nong Phai sub-district, Chum Phae district, Khon Kaen province, were found to be overall at the highest level. When considered in each item in the descending order, the aspect “Allowance provision procedures and the end of the elderly’s allowance” was found to be at the highest level, followed by the aspect “Procedures of application and eligibility,” and the aspect of “Characteristics of the eligible elderly” was found to be at the lowest level.           2) The comparison of problems of policy implementation on cash allowance provision under the elderly income guarantee project in Nong Phai sub-district, Chum Phae district, Khon Kaen province, was found that opinions of the elderly with different gender and educational level in Nong Phai sub-district, Chum Phae district, Khon Kaen province, were fount not to be different, but those of the elderly with different age were found to be different at a statistically significant level of .05.           3) The recommendations on the problems of policy implementation on cash allowance provision under the elderly income guarantee project in Nong Phai sub-district, Chum Phae district, Khon Kaen province, were in details as follows: (1) In terms of characteristics of the eligible elderly, the most frequent problem was lack of public relations on the characteristics of the eligible elderly, followed by community leaders’ cooperation failure on allowance provision for the elderly, and no documents, brochures and leaflets for the elderly. In terms of the problem solution, the opinion that the local administrative organization was required to publicize the people characteristics of the eligible elderly to receive the elderly allowance and available documents used to receive the elderly allowance was found to be most required, followed by the opinion that community leaders were required to publicize through the village’s public loudspeakers and to provide the elderly and their descendants with other related documents. (2) In terms of procedures of application and eligibility, the most frequent problem was the lack of public relations on procedures of application-form submission and eligibility examination, and on procedures of the elderly allowance receiving. As well, in terms of the problem solution, the opinion that community leaders should be frequently trained or informed procedures of the elderly allowance, which were publicized clearly to the elderly, was found to be most required, followed by the opinion that related documents of the elderly allowance should be provided the elderly’s descendants and frequently announced or publicized the elderly. And (3) the method of payment and termination of the elderly subsistence allowance. The most common problem was the delay in subsistence allowance, followed by the lack of public relations for the heirs. And if the elderly died in the middle to receive a subsistence allowance. The solution found out on the most telling steps, or how to inform the public. The second, the exact date of the monthly allowance payment, and give the dead to receive the last subsistence allowance.